The impact of key processing stages and flock variables on the prevalence and levels of Campylobacter on broiler carcasses. (May 2021) - Emanowicz, Malgorzata; Meade, Joseph; Bolton, Declan; Golden, Olwen; Gutierrez, Montserrat; Byrne, William; Egan, John; Lynch, Helen; O'Connor, Lisa; Coffey, Aidan; Lucey, Brigid; Whyte, Paul
Abstract: This study examined the impact of key processing stages and flock variables on the prevalence of Campylobacter on broiler carcasses. Overall, the prevalence of Campylobacter was 62% in caeca, and 68%, 65% and 62% in neck skin samples collected after evisceration, final wash and carcass chilling, respectively. Campylobacter were found in 32% of caeca, and 52%, 40% and 32% of neck skin samples collected after evisceration, final wash and carcass chilling, respectively from first thin broiler batches. Final thin broiler batches were more frequently contaminated with prevalences of 83% found in caeca, 80% in neck skin samples collected after evisceration and 83% found in neck skin samples collected after both final wash and carcass chilling stages (p < 0.05). Thinning status had a significant effect on Campylobacter counts with significantly higher counts observed in samples from final thin batches (p < 0.05). Highest Campylobacter concentrations in neck skin samples were observed at the evisceration stage in both first and final thin samples, with counts ranging from 2.0 to 3.8 log10 CFU/g and 2.3 to 4.8 log10 CFU/g in first and final thin batches, respectively. All first thin samples had counts below the European Union (EU) Process Hygiene Criterion threshold level of 3 log10 CFU/g after chilling while 52% of final thin batches had counts above this limit. Highlights: Flock weight, age and depopulation status were positively correlated with Campylobacter counts. Evisceration was identified as a high risk stage for introducing Campylobacter contamination. Significant reductions in Campylobacter counts were observed after carcass washing. Campylobacter counts in caeca and corresponding neck skin samples were positively correlated.